Journal of Instrumentation - Bogdanov physicist Associate Professor of Tomsk Polytechnic University, Candidate of Physical and Mathematical Sciences; Rozhkova physicist Associate Scientist of Tomsk Polytechnic University, candidate of physico-mathematical Sciences; Pivovarov physicist professor of Tomsk Polytechnic University; Kuzminchuk-Feuerstein (2018)
The first proof of principle experiment with a prototype of a Time-of-Flight (TOF) - Cherenkov detector of relativistic heavy ions (RHI) exploiting a liquid Iodine Naphthalene radiator has been performed at Cave C at GSI (Darmstadt, Germany). A conceptual design for a liquid Cherenkov detector was proposed as a prototype for the future TOF measurements at the SuperFRS by detection of total number of Cherenkov photons. The ionization energy loss of RHI in a liquid radiator decreases only slightly this number, while in a solid radiator changes sufficiently not the total number of ChR photons, but ChR angular and spectral distributions. By means of computer simulations, we showed that these distributions are very sensitive to the isotope mass, due to different stopping powers of isotopes with initial equal relativistic factors. The results of simulations for light (Li, Be) and heavy (Xe) isotopes at 500-1000 MeV/u are presented indicating the possibility to use the isotopic effect in ChR of RHI as the mass selector.